AWARENESS OF RHEUMATIC HEART DISEASE IN PATIENTS SUFFERING FROM RHEUMATIC HEART DISEASE - M Hamid Saeed1; Muhammad Shahzad Afzal (Journal of University Medical & Dental College, 2016)
ABSTRACT: OBJECTIVE: To determine the degree of awareness about the different aspects of rheumatic heart disease in patients coming to different departments of Faisalabad Institute of Cardiology, Faisalabad. STUDY DESIGN AND DURATION: Questionnaire based survey study, 2 weeks. PATIENTS AND METHODS: A total of 200 commutative patients of either sex between 12-80 years of age, suffering from Rheumatic Heart Disease coming to Faisalabad Institute of Cardiology were included in the study. RESULTS: Out of 200 patients included in the survey, 130 (65%) patients were females and 70 (35%) were male. Majority of the patients (78%) belonged to villages whereas 22% patients belonged to cities. 48.5% of the patients aged between 12-30 years of age, 31.5% aged between 31-45 years and 20% of patients aged 45 years and above. Only 5% of the patients were aware that sore throat is a precipitating factor for Rheumatic Heart Disease. 23% of the patients were aware of prolonged antibiotic prophylaxis. After diagnosis of the disease, 77% of the patients were aware of different treatment options available like valvuloplasty or valve replacement surgery. 58% of the patients were aware of prolonged oral anticoagulation and antibiotic prophylaxis after undergoing surgery. CONCLUSIONS: The patient population is lacking awareness about Rheumatic Heart Disease and treatment options available which has a profound effect on the incidence, morbidity and mortality of the disease. The study will help us to plan awareness strategies and their implementation by health department and the other measures of mass communication.